Evaluating Active Transport Benefits and Costs. Guide to Valuing Walking and Cycling Improvements and Encouragement Programs. - Litman, Todd (My University, 2021)
This report describes methods for evaluating the benefits and costs of active transport (walking, cycling, and their variants, also called non-motorized and human-powered travel). It describes various types of benefits, costs and methods for measuring them. These include direct benefits to users from improved active transport conditions, various benefits to society from increased walking and cycling activity, reduced motor vehicle travel, and more compact and multi-modal community development. It discusses active transport demands and ways to increase walking and cycling activity. This analysis indicates that many active transport benefits tend to be overlooked or undervalued in conventional transport economic evaluation
Keywords: Individualverkehr; Fahrradverkehr; Fußgängerverkehr; Kosten-Nutzen-Analyse; Wirkungsanalyse; Verkehrspolitik; Nichtmotorisierter Verkehr